Managing Guru PenggerakProgram: Insights from the Guru Penggerak Education Center” (BGP) Jambi Province, Indonesia - Witria Marta Lenti; Lantip Diat Prasojo; Resky Nuralisa Gunawan (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
This study describes the management of the Movers Teacher Education program and identifies the supporting and inhibiting factors in its implementation at the Guru Penggerak (Movers Teacher) Education Center (BGP) in Jambi Province, Indonesia. The study focuses on the effectiveness of program implementation within the context of education management. A qualitative research approach was used, with data collected from the BGP Jambi Province, including the Head of BGP, Head of the General Sub-Division, Program Implementation Coordinator, and Sub-coordinator of the Teacher Mover Program. Data were gathered through interviews, observations, and document studies, then analyzed using Miles,Huberman, and Saldana's six-step inductive analysis model. The findings indicate that program management is conducted through three main functions: planning, implementation, and evaluation, which align with the DG GTK policies. Planning involves strategy development and working group formation; implementation includes online learning, individual mentoring, and workshops; and evaluation is conducted using the LMS in SIMPKB and the SIMERDEKA application. Supporting factors for implementation include collaboration with BPMP and local education offices, while obstacles include limited human resources, scheduling mismatches, and geographical challenges in mentoring. The conclusion highlights that program management has been executed in accordance with management functions. These findings imply the importance of strengthening coordination and resource allocation to optimize the program